Implementasi Algoritma C5.0 Untuk Klasifikasi Kepuasan Masyarakat Terhadap Pelayanan Kantor Kecamatan - Rahmanita Widiyanti; Cucu Suhery; Rahmi Hidayati (JURIKOM (Jurnal Riset Komputer), 2022)
Public service is an activity to fulfill service needs for the people. Kecamatan Pontianak Kota Office is one of the institutes that perform public services. People's satisfaction with the services provided by the Kecamatan Pontianak Kota Office can be measured by a satisfaction survey in order to improve service quality. The existence of various assessment elements makes it difficult for the Kecamatan Pontianak Kota Office to determine people's satisfaction with services. Therefore, we need a system that can classify and determine the elements of the assessment that affect service satisfaction. In this research, the C5.0 algorithm was used to classify people's satisfaction. The assessment elements (variables) used for classification consist of suitability of services, understanding of procedures, speed of service, costs, service standards, officers' abilities, behavior of officers, facilities and infrastructure, and service complaints. This research resulted in a classification such as very good, good, and not good. The amount of data used is 250 data with training data used as much as 175 data and test data as much as 75 data. The C5.0 algorithm produces a decision tree, rules, and the ability of officers as an influential assessment element. Based on the test results obtained 90.67% accuracy, 68.085% precision, 55.89% recall, and 9.33% error rate